2016
DOI: 10.3748/wjg.v22.i31.7166
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus related fatal duodenal diverticular bleeding: Case report and literature review

Abstract: Involvement of gastrointestinal tract by cytomegalovirus (CMV) is common. CMV infections mainly run their course without any clinical signs in immunocompetent hosts. In contrast, CMV can cause severe infections with serious consequences in a immunocompromised state typically associated with organ transplants, highly immunosuppressive cancer chemotherapy, advanced HIV infection or treatment with corticosteroids. The incidence and severity of these manifestations of CMV is directly proportional with the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…CMV or EBV primary infection is usually asymptomatic in adults and children. In immunocompromised individuals, acute CMV infection may cause oral ulcers, periodontitis, sialadenitis, gingival hyperplasia, esophagitis, black esophagus, hepatitis, pancreatitis, gastritis, appendicitis, and among other clinical manifestations [ 34 , 35 ]. In immunocompetent individuals, the usual clinical symptoms include pharyngitis, lymphadenopathy, fever, and mononucleosis-like syndrome [ 36 ].…”
Section: Clinical Manifestations Of CMV and Ebv Infectionsmentioning
confidence: 99%
“…CMV or EBV primary infection is usually asymptomatic in adults and children. In immunocompromised individuals, acute CMV infection may cause oral ulcers, periodontitis, sialadenitis, gingival hyperplasia, esophagitis, black esophagus, hepatitis, pancreatitis, gastritis, appendicitis, and among other clinical manifestations [ 34 , 35 ]. In immunocompetent individuals, the usual clinical symptoms include pharyngitis, lymphadenopathy, fever, and mononucleosis-like syndrome [ 36 ].…”
Section: Clinical Manifestations Of CMV and Ebv Infectionsmentioning
confidence: 99%
“…This is the first known case report of life-threatening hemorrhage from CMV duodenitis managed successfully with surgery. Among the four CMV duodenitis case reports found during literature review, three manifested with life-threatening bleeding, only one patient survived [7], [8], [9], [10]. In the surviving case, CMV was identified emergently on histopathologic examination of endoscopic biopsy [9].…”
Section: Discussionmentioning
confidence: 98%
“…A 2011 study of CMV infection in the upper GI tract, found the stomach to be the most common site of involvement and only one out of thirty cases involved the duodenum [6] . Literature review identified four case reports of CMV duodenitis [7] , [8] , [9] , [10] , where all four cases involved immunocompromised patients. Presented here is an atypical case of CMV duodenitis causing life-threatening hemorrhage in an immunocompetent individual, with no history of immunosuppressive treatments or infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This infection is transmitted during birth, breastfeeding, sexual contact, organ transplant, or transfusion. This viral disease is prevalent in adults by involving 50-80% of the general population, representing an antibody to CMV by the age of 35 years [8].…”
Section: Discussionmentioning
confidence: 99%